Penerapan Strategi Pembelajaran Ekspositori dalam Meningkatkan Kompetensi Komunikasi Peserta Didik Era Digital - Dea Permata; Sari Handayani; Gusmaneli Gusmaneli (Harmoni Pendidikan : Jurnal Ilmu Pendidikan, 2025)
This study aims to explore the implementation of expository teaching strategies in enhancing students' communication competencies in the digital era. Using a qualitative research method with a library research approach, this study analyzes various literatures related to expository teaching, communication competencies, and the use of digital technology in education. The findings reveal that expository teaching supported by digital technology can enrich the learning experience by increasing interactivity, accessibility, and understanding of the material. However, challenges such as the digital divide, digital distractions, and the need for adequate digital literacy skills were also identified. In conclusion, while the implementation of expository teaching based on technology offers numerous benefits, proper management and adequate training support for both teachers and students are crucial to maximize learning outcomes.